Discomfort Intolerance Scale: A Study of Reliability and Validity - Kadir ÖZDEL; Özden YALÇINKAYA ALKAR; İbrahim TAYMUR; M. Hakan TÜRKÇAPAR; Erkut ZAMKI; A. Emre SARGIN (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Discomfort Intolerance Scale was developed by Norman B. Schmidt et al. to assess the individual differences of capacity to withstand physical perturbations or uncomfortable bodily states (2006). The aim of this study is to investigate the validity and reliability of Discomfort Intolerance Scale-Turkish Version (RDÖ). Method: From two different universities, total of 225 students (male=167, female=58) were participated in this study. In order to determine the criterion validity, Beck Anxiety Inventory (BAI) and State-Trait Anxiety Inventory (STAI) were used. Construct validity was evaluated by factor analysis after the Kaiser-Meyer-Olkin (KMO) and Barlett test had been performed. To assess the test-retest reliability the scale was re-applied to 54 participants 6 weeks later. Results: To assess construct validity of DIS, factor analyses were performed using varimax principal components analysis with varimax rotation. The factor analysis resulted in two factors named “discomfort (in) tolerance” and “discomfort avoidance”. The Cronbach’s alpha coefficient for the entire scale, discomfort-(in)tolerance subscale, discomfortavoidance subscale were, .592, .670, .600 respectively. Correlations between two factors of DIS, discomfort intolerance and discomfort avoidance, and Trait Anxiety Inventory of STAI (State-Trait Anxiety Inventory) were statistically significant at the level of 0.05. Test-retest reliability was statistically significant at the level of 0.01. Conclusion: Analysis demonstrated that DIS had a satisfactory level of reliability and validity in Turkish university students.